Apheloria polychroma, a new species of millipede from the Cumberland Mountains (Polydesmida: Xystodesmidae) - Marek, Paul E.; Means, Jackson C.; Hennen, Derek A. (Zootaxa, 2018)
Millipedes of the genus Apheloria Chamberlin, 1921 occur in temperate broadleaf forests throughout eastern North America and west of the Mississippi River in the Ozark and Ouachita Mountains. Chemically defended with toxins made up of cyanide and benzaldehyde, the genus is part of a community of xystodesmid millipedes that compose several Müllerian mimicry rings in the Appalachian Mountains. We describe a model species of these mimicry rings, Apheloria polychroma n. sp., one of the most variable in coloration of all species of Diplopoda with more than six color morphs, each associated with a separate mimicry ring.